Quantitative analysis of fourteen heterocyclic aromatic amines in bakery products by a modified QuEChERS method coupled to ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). (15th November 2019) - Wu, Yuluan; Chen, Liwei; Xian, Yanping; Hou, Xiangchang; Liang, Ming; Dong, Hao; Chen, Jiefeng
Highlights: First report for simultaneous analysis of HAAs in bakery products by UHPLC-MS/MS. QuEChERS provides satisfactory clean-up for HAAs analysis in bakery products matrix. The method with favorable sensitivity and selectivity is easy to implement. The method is a good tool enabling detection of HAAs in bakery products. HAAs such as harman, norharman, AaC, PhIP are widely detected in bakery products. Abstract: Heterocyclic aromatic amines (HAAs) are harmful by-products naturally formed during the heating process of foodstuffs. The present work reported an analytical method for HAAs analysis for the first time in bakery products by QuEChERS technique combined with ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). Bakery products were ultrasonically extracted with acetonitrile and sodium hydroxide solution (1 mmol/L). The obtained extracting solution was nearly dried under nitrogen stream and subsequently purified by QuEChERS technique using primary secondary amine (PSA) as adsorbents. Fourteen HAAs were separated on a C18 column with the mobile phase of a mixture of acetonitrile and 1 mmol/L ammonium acetate water solution (containing 0.04% acetic acid), and detected by MS/MS under multiple reaction monitoring (MRM) mode. The developed method was validated in terms of linearity, matrix effect, accuracy and precision. The method showed a good linearity (R 2  > 0.999) for all analytes in their corresponding concentration ranges. The method limit of quantifications (LOQs, S/N = 10) of 14 HAAs were in the range of 0.3–4.5 μg/kg. The average recoveries (n = 6) at 3 spiked levels ranged from 62.8 to 96.8% with relative standard deviations (RSDs) of 1.2–7.6%. The validated method was applied in HAAs analysis in 20 bakery products and 4 kinds of HAAs (harman, norharman, AaC, PhIP) were detected with the concentrations ranging from 0.6 to 35.6 μg/kg.